Using the common criteria for IT security evaluation - Herrmann, Debra S. (Auerbach Publications, 2003)
This book "explains how and why to use the 'common criteria' during the acquisition, implementation or evaluation of an IT product, system, network or services contract. The text describes the 'common criteria' methodology ; the major processes, steps, activities, concepts, terminology, and how the CC methodology is used throughout the life of a system."--Back cover